Signifikansi Teori-Teori Popper, Kuhn, dan Lakatos Terhadap Pengembangan Ilmu-Ilmu Keislaman - Rofiq, Ahmad Choirul (Ulumuna, 2017)
One of the contemporary problems being experienced by Muslims is their backwardness in current science development. The progress of science in general is currently dominated by the West. Theme of this paper is the development of science and emergence of theories around it. To elaborate the theme the author will first briefly review the sequence of the development of science in the path of history to show the positive contributions of Muslims. Next is the analysis of theories proposed by Popper, Kuhn and Lakatos. After that, this paper attempt to describe the significance of these theories to the development of Islamic sciences while connecting them with Fazlur Rahman’s view about normative Islam and historical Islam in order to obtain an alternative portrait of the direction of future development.